Pembentukan Karakter Digital Berbasis Nilai Keagamaan melalui Pelatihan Jaringan Komputer di SMP Nusantara Kota Sorong - Agnes, Melda; Leuwwo, Natasya; Uktolseja, Lulu Jola; Gede, Gede; Marsya, Marsya; Kelvin, Kelvin; Etha, Etha; Gerynando, Gerynando; Herman, Herman (CV. Era Digital Nusantara, 2026)
The development of information technology requires the younger generation to not only have digital skills, but also strong character based on moral and religious values. This community service activity aims to shape the digital character of students at Nusantara Junior High School in Sorong City through computer network cabling training combined with the instillation of values of discipline, responsibility, cooperation, and integrity as socio-religious values. The implementation of the activity included needs assessment, socialization, material delivery, practical training, and evaluation. The training focused on introducing network devices, protocol configure, cabling techniques using UTP cables, installing RJ-45 connectors, using crimping pliers, and testing the results using a LAN tester. The results of the activity show that students not only understand the basic concepts of computer networks and are able to carry out cabling practices independently, but also show an increase in positive attitudes such as accuracy, teamwork, and discipline during the training process. This activity shows that combining digital literacy and religious values can be an effective strategy in shaping students' digital character while improving their technical competence in the technological era.